Widespread learned predator recognition to an alien predator across populations in an amphibian species - Nuria Polo-Cavia; Rosa Arribas; Carlos Caballero-Díaz; Ángel Baltanás; Ivan Gomez-Mestre (Scientific Reports, 2023)
Abstract Alien predators are a major cause of decline and extinction of species worldwide, since native organisms are rarely equipped with specific antipredatory strategies to cope with them. However, phenotypic plasticity and learned predator recognition may help prey populations to survive novel predators. Here we examine geographical variation in the learning ability of larval spadefoot toads (Pelobates cultripes) to recognize invasive predatory crayfish (Procambarus clarkii). We compare the learning-mediated behavioural responses of tadpoles from six populations across two regions in Spain (central and southern), with different histories of exposure to the presence of the invasive species. Two of the populations showed innate recognition of chemical cues from the invasive crayfish, whereas three of them learned to recognize such cues as a threat after conditioning with conspecific alarm cues. Learning abilities did not differ among southern populations, but they did among central populations. We assessed patterns of genetic variation within and among these two regions through microsatellite markers and found low genetic divergence among the southern populations but greater differentiation among the central ones. We hypothesize that similar responses to the invasive crayfish in southern populations may have arisen from a combination of extended historical exposure to this introduced predator (~ 50 y) and higher levels of gene flow, as they inhabit a highly interconnected pond network. In contrast, populations from central Spain show lower connectivity, have been exposed to the invasive crayfish for a shorter period of time, and are more divergent in their plastic responses.